Die Strassenfegerinnen von Addis Abeba . Sweeping Addis - Kuenzli, Corinne (Franziska Reck, 2007)
Verzio FF submission Addis Ababa, capital of Ethiopia with four million inhabitants, on a rainy day. A glance out the window of a moving car zooms in on shrouded female figures. With circumspection and respect, filmmaker Corinne Kuenzli wins the confidence of these female street-sweepers, and they allow her to film them. Their job is to beautify and modernize the city. Just recently the number of jobs cleaning the streets was doubled - to 1000. It is a sought-after job. The street sweepers have no bank accounts. Their security comes from their religion and the mutual support they give each other. The women join forces, save money together and help one another. In the privacy of their own homes, they remove their coverings, tell their life stories, speak about their worries and misery but also of their happiness and wishes for the future. A multifaceted portrait of four remarkable Ethiopian women, coping with life in a land marked by uncertainty and political tension.